2006
DOI: 10.1111/j.0030-1299.2006.14547.x
|View full text |Cite
|
Sign up to set email alerts
|

Can prey behaviour induce spatially synchronic aggregation of solitary predators?

Abstract: M. 2006. Can prey behaviour induce spatially synchronic aggregation of solitary predators? Á Oikos 113: 497 Á505.Spatio-temporal patterns of predator aggregations within their settlement areas (i.e. temporary settling zones used during dispersal or, more generally, foraging patches) were studied. By integrating the main behavioural rules of juveniles of Spanish imperial eagles Aquila adalberti during dispersal with the temporal availability of the eagles' main prey, we have developed several individual-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…This implies that it may be unwise to monitor only the breeding part of a population because of the potential delay in detecting a decline, underestimating the extent of a decline and overestimating recovery levels (Kokko & Sutherland, 1998;Kenward et al, 2000). More generally, Penteriani et al (2005bPenteriani et al ( , 2006a found that: (1) the survival of dispersing individuals (the numbers of which depend on the productivity in breeding areas) is highly dependent on the number of available settlement areas and their resources; (2) environmental stochasticity has a greater influence on the entire population (breeders+floaters) when variations in environmental conditions occur in a synchronous way (i.e. simultaneously in both the settlement and breeding areas).…”
Section: How the Fate Of Floaters Can Affect The Stability Of Breedinmentioning
confidence: 99%
“…This implies that it may be unwise to monitor only the breeding part of a population because of the potential delay in detecting a decline, underestimating the extent of a decline and overestimating recovery levels (Kokko & Sutherland, 1998;Kenward et al, 2000). More generally, Penteriani et al (2005bPenteriani et al ( , 2006a found that: (1) the survival of dispersing individuals (the numbers of which depend on the productivity in breeding areas) is highly dependent on the number of available settlement areas and their resources; (2) environmental stochasticity has a greater influence on the entire population (breeders+floaters) when variations in environmental conditions occur in a synchronous way (i.e. simultaneously in both the settlement and breeding areas).…”
Section: How the Fate Of Floaters Can Affect The Stability Of Breedinmentioning
confidence: 99%
“…The ease of rabbit capture, as suggested by the hunting behaviour of tagged owls, could be also supported by the activity rhythms and habitat use of rabbits in Mediterranean Spain (Moreno et al 1996, Penteriani et al 2006a, where the number of diurnal and more visible predators is higher than nocturnal ones. As a consequence, the risk of predation is higher during daylight hours and rabbits (Villafuerte 1994, Moreno et al 1996: (1) prefer to feed close to cover during the day, whereas use open habitat at night, becoming highly visible and easy to pursue prey for eagle owls, and (2) are more active at night than during the day, increasing their rate of owl encounters.…”
Section: Discussionmentioning
confidence: 93%
“…Previous work has illustrated how the survival of the reproductive portions of a population is strongly dependent on the dynamics of floaters, on the number of available settlement areas (i.e., temporary settling zones used by juveniles during natal dispersal) and on the type of fluctuations between the floating and breeding portions of a population (Penteriani et al 2005a). In addition, the availability of the main prey types influences dispersal movements among the different settlement areas (Penteriani et al 2006a), and an increase in the mortality rate within settlement areas can dramatically affect the stability and persistence of breeders (Penteriani et al 2005b). Finally, the patterns and dynamics that are observed in the breeding sectors of a population may have their origin in the patterns and dynamics that occur in the settlement areas during dispersal (Ferrer and Penteriani 2008, Penteriani et al 2006b).…”
Section: Pensamientos Sobre La Dispersió N Natalmentioning
confidence: 99%